Microbial, Physicochemical and Nutritional Quality Assessment of Fruit Juices in Tangail Municipality, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Analysis of the microbial, physicochemical and nutritional qualities of some commercially bottled and handmade fruit juices showed that total viable bacteria in bottle juices ranged from 9.6×107 to 2.0×1011 cfu/100 ml and handmade juices 1.3×105 to 9.6×107 cfu/100 ml. The log mean values of total bacteria count ranged from 9.14-10.19 cfu/100 ml (bottled) and 6.09-9.08 cfu/100 ml (handmade).Total coliform bacteria ranged from 0-7.6×109 cfu/100 ml (bottled) and 0 - 2.8×105 cfu /100 ml (handmade) with a range of log mean values of 3.18-6.95 cfu/100 ml (bottled) and 3.47-3.48 cfu/100 ml (handmade). The pH was acidic and mean value ranged from 3.14-4.03 for bottled juice and 3.72-3.73 (handmade). It was found that total soluble solids ranged from 10-11.33% for bottle and 11.33-12.33% for handmade juices. The concentration of vitamin C in bottled and handmade juices ranged from 0.74-2.22 mg/100 ml and 2.34-3.7 mg/100 ml, respectively, indicated that vitamin C content was very low. It was also revealed that quality of bottled and handmade juices was unsatisfactory and may not be useful for consumption. It is suggested that proper measure must be taken and manufacturing companies should develop the quality by maintaining hygiene and using good quality ingredients in preparing different types of juices.J. Asiat. Soc. Bangladesh, Sci. 46(1): 37-47, June 2020